Question
upstudy study bank question image url

4. Draw a sketch graph of \( f(x)=\left(\frac{1}{3}\right)^{x} \). 4.1 Give the domain and range of \( f \). 4.2 For which values of \( x \) is \( f(x)>0 \) ? 4.3 Give the coordinates of any three points on \( f \). 4.4 Give the equation of \( g \) if \( g \) is formed when the graph of \( f \) is moved 3 units down. 4.5 Give the equation of \( h \) if \( h \) is formed when the graph of \( f \) is moved 3 units left. 4.6 Give the equation of \( k \) if \( k \) is formed when the graph of \( f \) is moved 2 units upwards and 3 un to the right. 4.7 Give the domain and range of \( g \). 4.8 Give the domain and range of \( h \). 4.9 Give the domain and range of \( k \). 4.10 Give the asymptotes of \( f, g, h \) and \( k \).

Ask by Higgins Mathis. in South Africa
Feb 19,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

**Summary of Results:** 1. **Function \( f(x) = \left(\frac{1}{3}\right)^{x} \)** - **Domain**: All real numbers (\( (-\infty, \infty) \)) - **Range**: Positive real numbers (\( (0, \infty) \)) - **\( f(x) > 0 \)**: For all real \( x \) - **Three Points**: \( (0, 1) \), \( (1, \frac{1}{3}) \), \( (-1, 3) \) 2. **Transformed Functions:** - **\( g(x) \)**: \( g(x) = \left(\frac{1}{3}\right)^{x} - 3 \) - **\( h(x) \)**: \( h(x) = \left(\frac{1}{3}\right)^{x + 3} \) - **\( k(x) \)**: \( k(x) = \left(\frac{1}{3}\right)^{x - 3} + 2 \) 3. **Properties of Transformed Functions:** - **\( g(x) \)** - **Domain**: All real numbers (\( (-\infty, \infty) \)) - **Range**: \( (-3, \infty) \) - **\( h(x) \)** - **Domain**: All real numbers (\( (-\infty, \infty) \)) - **Range**: \( (0, \frac{1}{27}) \) - **\( k(x) \)** - **Domain**: All real numbers (\( (-\infty, \infty) \)) - **Range**: \( (2, \infty) \) 4. **Asymptotes:** - All functions \( f, g, h, k \) have a horizontal asymptote at \( y = 0 \). **Conclusion:** The function \( f(x) = \left(\frac{1}{3}\right)^{x} \) is an exponential function with a domain of all real numbers and a range of positive real numbers. When transformed, the functions \( g, h, \) and \( k \) maintain the exponential nature but shift vertically and horizontally, affecting their ranges and positions on the graph. All transformed functions share a common horizontal asymptote at \( y = 0 \).

Solution

Function by following steps: - step0: Find the y-intercept: \(g\left(x\right)=3^{-x}-3\) - step1: Set \(x\)=0\(:\) \(g\left(0\right)=3^{-0}-3\) - step2: Evaluate: \(g\left(0\right)=3^{0}-3\) - step3: Evaluate the power: \(g\left(0\right)=1-3\) - step4: Subtract the numbers: \(g\left(0\right)=-2\) Analyze the y intercept of the function \( k(x)=(\frac{1}{3})^{x-3}+2 \) Function by following steps: - step0: Find the y-intercept: \(k\left(x\right)=3^{-x+3}+2\) - step1: Set \(x\)=0\(:\) \(k\left(0\right)=3^{-0+3}+2\) - step2: Evaluate: \(k\left(0\right)=3^{0+3}+2\) - step3: Simplify: \(k\left(0\right)=29\) Analyze the y intercept of the function \( f(x)=(\frac{1}{3})^{x} \) Function by following steps: - step0: Find the y-intercept: \(f\left(x\right)=\left(\frac{1}{3}\right)^{x}\) - step1: Set \(x\)=0\(:\) \(f\left(0\right)=\left(\frac{1}{3}\right)^{0}\) - step2: Evaluate the power: \(f\left(0\right)=1\) Analyze the y intercept of the function \( h(x)=(\frac{1}{3})^{x+3} \) Function by following steps: - step0: Find the y-intercept: \(h\left(x\right)=\left(\frac{1}{3}\right)^{x+3}\) - step1: Set \(x\)=0\(:\) \(h\left(0\right)=\left(\frac{1}{3}\right)^{0+3}\) - step2: Remove 0: \(h\left(0\right)=\left(\frac{1}{3}\right)^{3}\) - step3: Simplify: \(h\left(0\right)=\frac{1}{27}\) Find the horizontal asymptotes of \( f(x)=(\frac{1}{3})^{x} \). Function by following steps: - step0: Find the horizontal asymptotes: \(f\left(x\right)=\left(\frac{1}{3}\right)^{x}\) - step1: Find the horizontal asymptotes: \(\textrm{No horizontal asymptotes}\) Find the horizontal asymptotes of \( k(x)=(\frac{1}{3})^{x-3}+2 \). Function by following steps: - step0: Find the horizontal asymptotes: \(k\left(x\right)=3^{-x+3}+2\) - step1: Find the horizontal asymptotes: \(\textrm{No horizontal asymptotes}\) Find the horizontal asymptotes of \( h(x)=(\frac{1}{3})^{x+3} \). Function by following steps: - step0: Find the horizontal asymptotes: \(h\left(x\right)=\left(\frac{1}{3}\right)^{x+3}\) - step1: Find the horizontal asymptotes: \(\textrm{No horizontal asymptotes}\) Find the horizontal asymptotes of \( g(x)=(\frac{1}{3})^{x}-3 \). Function by following steps: - step0: Find the horizontal asymptotes: \(g\left(x\right)=3^{-x}-3\) - step1: Find the horizontal asymptotes: \(\textrm{No horizontal asymptotes}\) Let's solve the problem step by step. ### 4. Sketch Graph of \( f(x) = \left(\frac{1}{3}\right)^{x} \) 1. **Domain and Range of \( f \)**: - The function \( f(x) = \left(\frac{1}{3}\right)^{x} \) is defined for all real numbers \( x \). - As \( x \) approaches infinity, \( f(x) \) approaches 0 but never reaches it. As \( x \) approaches negative infinity, \( f(x) \) approaches infinity. - Therefore, the domain is \( (-\infty, \infty) \) and the range is \( (0, \infty) \). 2. **Values of \( x \) for which \( f(x) > 0 \)**: - Since \( f(x) = \left(\frac{1}{3}\right)^{x} \) is an exponential function, it is always positive for all real \( x \). - Thus, \( f(x) > 0 \) for all \( x \in (-\infty, \infty) \). 3. **Coordinates of Three Points on \( f \)**: - Let's calculate three points: - \( f(0) = \left(\frac{1}{3}\right)^{0} = 1 \) → Point: \( (0, 1) \) - \( f(1) = \left(\frac{1}{3}\right)^{1} = \frac{1}{3} \) → Point: \( (1, \frac{1}{3}) \) - \( f(-1) = \left(\frac{1}{3}\right)^{-1} = 3 \) → Point: \( (-1, 3) \) 4. **Equation of \( g \)** (moved 3 units down): - The equation of \( g \) is \( g(x) = f(x) - 3 = \left(\frac{1}{3}\right)^{x} - 3 \). 5. **Equation of \( h \)** (moved 3 units left): - The equation of \( h \) is \( h(x) = f(x + 3) = \left(\frac{1}{3}\right)^{x + 3} = \left(\frac{1}{3}\right)^{x} \cdot \left(\frac{1}{3}\right)^{3} = \frac{1}{27} \left(\frac{1}{3}\right)^{x} \). 6. **Equation of \( k \)** (moved 2 units upwards and 3 units to the right): - The equation of \( k \) is \( k(x) = f(x - 3) + 2 = \left(\frac{1}{3}\right)^{x - 3} + 2 \). 7. **Domain and Range of \( g \)**: - The domain of \( g \) is the same as \( f \): \( (-\infty, \infty) \). - The range of \( g \) is \( (-3, \infty) \) since it shifts down by 3. 8. **Domain and Range of \( h \)**: - The domain of \( h \) is \( (-\infty, \infty) \). - The range of \( h \) is \( (0, \frac{1}{27}) \) since it is a scaled version of \( f \). 9. **Domain and Range of \( k \)**: - The domain of \( k \) is \( (-\infty, \infty) \). - The range of \( k \) is \( (2, \infty) \) since it shifts up by 2. 10. **Asymptotes of \( f, g, h, \) and \( k \)**: - All functions have a horizontal asymptote at \( y = 0 \) since they approach 0 as \( x \) approaches infinity. ### Summary of Results: - **Domain of \( f \)**: \( (-\infty, \infty) \) - **Range of \( f \)**: \( (0, \infty) \) - **Values of \( x \) for \( f(x) > 0 \)**: All \( x \in (-\infty, \infty) \) - **Three Points on \( f \)**: \( (0, 1), (1, \frac{1}{3}), (-1, 3) \) - **Equation of \( g \)**: \( g(x) = \left(\frac{1}{3}\right)^{x} - 3 \) - **Equation of \( h \)**: \( h(x) = \left(\frac{1}{3}\right)^{x + 3} \) - **Equation of \( k \)**: \( k(x) = \left(\frac{1}{3}\right)^{x - 3} + 2 \) - **Domain of \( g \)**: \( (-\infty, \infty) \) - **Range of \( g \)**: \( (-3, \infty) \) - **Domain of \( h \)**: \( (-\infty, \infty) \) - **Range of \( h \)**: \( (0, \frac{1}{27}) \) - **Domain of \( k \)**: \( (-\infty, \infty) \) - **Range of \( k \)**: \( (2, \infty) \) - **Asymptotes**: All functions have a horizontal asymptote at \( y = 0 \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To sketch the graph of \( f(x) = \left(\frac{1}{3}\right)^{x} \), imagine a smoothly descending curve that approaches the x-axis but never quite touches it. As x increases, the function values decrease, showcasing an exponential decay. The domain of \( f \) is all real numbers, while the range is all positive real numbers (\( f(x) > 0 \)). For \( f(x) > 0 \), all x-values suffice, reinforcing that this function never reaches or dips below zero. Three points on \( f \) could be (0, 1), (1, \(\frac{1}{3}\)), and (-1, 3). If we move \( f \) down by 3 units to form \( g \), the equation becomes \( g(x) = \left(\frac{1}{3}\right)^{x} - 3 \). For \( h \), moving \( f \) left by 3 units results in \( h(x) = \left(\frac{1}{3}\right)^{(x + 3)} \). The equation for \( k \), with shifts of 2 units up and 3 units to the right, would be \( k(x) = \left(\frac{1}{3}\right)^{(x - 3)} + 2 \). The domain of \( g \) and \( h \) remains all real numbers, while the range of \( g \) is \( (-3, \infty) \), the same for \( h \) as this function only shifts left without affecting its positive nature. The range of \( k \), however, is \( (2, \infty) \). For asymptotes, they are all \( y = 0 \) for \( f \), \( g \) and \( h \); for \( k \), the asymptote shifts to \( y = 2 \).

Related Questions

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy